درجة ممارسة معلمي الأحياء لمهارات التفكير الناقد بمدارس التعليم ما بعد الأساسي في محافظة ظفار: The Degree of Biology Teachers’ Practice of Critical Thinking Skills in Post-Basic Education Schools in Dhofar Governorate - Amer Alawaed, Mohammed Salem (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث هدف هذا البحث إلى تعرف على درجة ممارسة معلمي الأحياء بمدارس محافظة ظفار لمهارات التفكير الناقد والمتمثلة بالتفسير والاستنباط وتقويم الحجج والاستنتاج في أثناء الموقف التعليمي داخل الصف، ولتحقيق ذلك تم استخدام المنهج الوصفي، حيث طبقت بطاقة ملاحظة على مجتمع البحث المكون من (25) معلم ومعلمة أحياء في مدارس ما بعد الأساسي بولاية صلالة. وأظهرت نتائج البحث أن درجة ممارسة معلمي الأحياء لمهارات التفكير الناقد في مدارس ما بعد التعليم الأساسي بمحافظة ظفار متوسطة لكل من مهارة (التفسير، تقويم الحجج والأفكار، الاستنباط) وضعيفة (مهارة الاستنتاج)، وأنه لا توجد فروق ذات دلالة إحصائية بين معلمي الأحياء في درجة ممارسة مهارات التفكير الناقد تعزى لمتغير النوع، بينما أظهرت النتائج وجود فروق ذات دلالة إحصائية في درجة ممارسة معلمي الأحياء لمهارات التفكير الناقد في مدارس ما بعد الأساسي بمحافظة ظفار تعزى لمتغير سنوات الخبرة. وفي ضوء النتائج أوصى الباحث بتزويد معلمي الأحياء بدليل استخدام مهارات التفكير الناقد يتضمن فلسفة التفكير وأهميته والاستراتيجيات القائمة عليه، وتنفيذ ورش تدريبية لمعلمي الأحياء حديثي التعيين بغرض إتقان مهارات التفكير الناقد عملياً. ABSTRACT The aim of this study was to identify the extent to which biology teachers in the schools of Dhofar Governorate practice critical thinking skills—specifically interpretation, inference, evaluation of arguments, and deduction—during classroom teaching. To achieve this, the descriptive method was employed, using an observation checklist applied to the research population, which consisted of 25 male and female biology teachers in post-basic education schools in the Wilayat of Salalah.The results of the study showed that the level of biology teachers' practice of critical thinking skills in post-basic education schools in Dhofar Governorate was moderate in the skills of interpretation, evaluation of arguments and ideas, and inference, but low in the skill of deduction. The results also revealed no statistically significant differences in the level of practicing critical thinking skills among biology teachers based on gender. However, there were statistically significant differences based on years of teaching experience.In light of these findings, the researcher recommended providing biology teachers with a guide for using critical thinking skills that includes the philosophy of thinking, its importance, and related strategies. The study also recommended conducting training workshops for newly appointed biology teachers to help them master the practical application of critical thinking skills.